Dietary effect of moringa (Moringa oleifera; Lamarck, 1785) leaf powder on growth response of tilapia (Oreochromis niloticus; Linnaeus, 1758) (Asian Journal of Medical and Biological Research, 2021)
Management of fish health is one of the main considerations in aquaculture and different plant compounds are being used for supporting fish health to minimize the negative impacts of synthetic aqua drugs. In the present experiment, potentiality of moringa (Moringa oleifera; Lamarck, 1785) leaf as a nutritious dietary source for tilapia (Oreochromis niloticus; Linnaeus, 1758) fish was tested and the duration was two months from 30th September to 30th November, 2020. The moringa leaves were brought, cleaned, dried, and finally crushed into powder. Three experimental diets were formulated using the processed moringa leaf powder (MLP) at the rate of 0% (MLP0%) as control, 10% (MLP10%) and 20% (MLP20%) as treatment mixing with rice bran, wheat bran, mustard oil cake, fish meal, soya oil and vitamin-mineral premix. Fifteen tilapia fingerlings having average initial length 10.88±0.11 cm and initial weight 29.06±0.50 g was stocked in each tank with 90 L water. Sixty days feeding trial was performed with three replications of each treatment. The fishes were fed with formulated feeds twice daily at 9 am and 4 pm at a rate of 3% of their body mass. Sampling of fish and water quality parameters were carried out at twelve days interval. Moreover, the blood glucose and cholesterol of tilapia were measured monthly. Final length, final weight, weight gain, percent weight gain, feed conversion ratio (FCR), specific growth rate (SGR) and production of tilapia were significantly different among the treatments. The highest FCR (3.17±0.25) and SGR (1.33±0.12 %) values were in MLP20% and MLP10%, respectively. In the experiment, the highest and the lowest tilapia production were 9.21±0.39 and 7.39±0.35 kg m-3 in MLP10% and MLP20%, respectively. The blood glucose values were significantly different among the treatments (p< 0.05) and the highest value was in MLP0% (48.00±2.00 mg dl-1). Moreover, the highest and the lowest blood cholesterol was found in MLP0% (177.67±2.52 mg dl-1) and MLP20% (148.33±1.53 mg dl-1), respectively whereas the values were highly significantly different among the treatments (p≤ 0.01). Water quality parameters were statistically similar among the treatments (p> 0.05) and the values were within acceptable range for tilapia culture.Asian J. Med. Biol. Res. 2021, 7 (2), 153-163